1970
DOI: 10.1152/ajplegacy.1970.219.5.1386
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of vasoactive substances in exercise hyperemia: O2, K+, and osmolality

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

1971
1971
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Skinner and Powell (30) have shown that potassium ions and decreased P02 have an additive effect in the production of decreased vascular resistance. It now appears that there is a similar relationship between elevated osmolarity and lowered Po 2 (31). The biphasic responses at low constant-flow perfusion in the current study support the idea that two or more agents participate iji the control of vascular resistance.…”
Section: Mohrman Cant Sparkssupporting
confidence: 82%
“…Skinner and Powell (30) have shown that potassium ions and decreased P02 have an additive effect in the production of decreased vascular resistance. It now appears that there is a similar relationship between elevated osmolarity and lowered Po 2 (31). The biphasic responses at low constant-flow perfusion in the current study support the idea that two or more agents participate iji the control of vascular resistance.…”
Section: Mohrman Cant Sparkssupporting
confidence: 82%
“…Classic studies of functional vasodilation in response to contractile activity had focused on the regulation of tissue oxygen pressure (pO 2 ) [2, 3] and the ability of “vasodilator substances” produced by active skeletal muscle fibers to relax vascular smooth muscle cells (SMCs) [12, 13]. In practice, functional vasodilation entails the ability to override (i.e., “escape”) sympathetic vasoconstriction [10, 11, 14] through mechanisms that – remarkably – are still being resolved.…”
Section: Background and Perspectivementioning
confidence: 99%
“…Oxygen has been reported to alter the response of the peripheral vasculature to potassium (19,20,26). Since the solution Po 2 was rather arbitrarily set at low levels, the effect of potassium at higher solution Po 2 levels was also investigated.…”
Section: 8 Dulingmentioning
confidence: 99%
“…Many investigators have shown that potassium at the increased concentrations observed in venous blood during exercise and hypoxia can relax smooth muscle both in vivo (5)(6)(7)(8)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) and in vitro (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Therefore, this ion.…”
mentioning
confidence: 99%